Effect of a reverse diet kit on the regression of atherosclerosis plaque and its effect on the lipid profile in patients with coronary artery disease - Sane, Rohit; Mandole, Rahul; Amin, Gurudatta; Ghadigaonkar, Pravin (International Journal of Research in Medical Sciences, 2024)
Background: Prevalence of coronary artery disease (CAD) constitutes a major public health problem in developing countries. CAD also represents a major economic burden on health care systems and eventually creates a large gap in the quality of care associated with the disease. Methods: To study ayurveda based disease and symptoms modifying therapy (Dietary modification and panchakarma therapy) to reduce symptoms of CHF and IHD and focus on reduction of total atheroma volume (TAV); plaque burden by a scientifically designed kit (Reverse diet kit) by Madhavbaug using a pre and post-test experimental design for patients with CAD. Results: At the end of 90 days, a coronary CT angiogram revealed that TAV decreased significantly by 71.76 mm3 in post-intervention plaque volume compared with baseline in the three major epicardial branches of the coronary artery. Conclusions: The data provided relevant real-world evidence that the ‘Reverse Diet Kit’ can modulate coronary artery plaque deposition by reducing lipid infiltration within the coronary plaque and may lead to disease reversal wherein panchakarma therapy enabled symptom management and helped improve cardiovascular outcomes in patients with CAD.